PUBLIC POLICYWG PRODUCTION IN 15th BRAZILIAN CONGRESS ON SCIENCE OF SPORTS: A READING OF IT SCIENCE CURRENT PRODUCTION (Fiep Bulletin - online, 2013)
In this trial we propose to examine some aspects contained in papers presented at the Working Group for Public Policy (WG 10) of the 15th Brazilian Congress of Science of Sports, viewing the guidance of the scientific literature of the area from the selected works.
Keywords: public policy; theoretical guidance; sports and leisure